Influence of Physical Evidence on Service Brand Image Dimensions and Brand Equity - Mukherjee, Somnath; Shivani, Shradha (Indian Journal of Marketing, 2013)
Branding and brand equity benefits have long been established for goods. Services which are said to be unique and different from goods in view of its unique characteristics need a different approach. The marketers have been trying to influence the consumers through the various marketing mix elements. In services, apart from the traditional mix elements, there are additional elements that hold relevance, collectively referred to as extended marketing mix elements. Among the elements, physical evidence has a definitive influence on brand image and subsequent brand equity. Services are high in experience quality, are personal in nature, and the consumers’ experience with the service firm is a key determinant to image perception and brand equity. Physical evidence encompasses the overall experience for the consumer and even the people element, another mix element, which includes the employees and the customers, who interact within the physical environment. A positive experience significantly affects the firm’s brand equity. There is a dearth of research in the area of marketing mix influence on brand equity in the area of services .The present paper tries to empirically investigate the influence of physical evidence on brand image dimensions like user image, corporate image, and service image and consequently, brand equity in services through a study carried out in the retail banking sector. The findings hold significant value for marketers by aiding them in identifying the influence pattern.